Subjects evidence of crimes committed medical staff for carrying out their proffesional duties (Journal of actual problems of jurisprudence, 2018)
The article is devoted to actual problems of crime in health care. Copyright in this article examines subjective sides compositions crimes in health care. In this research paper considers the views of national and Soviet scientists. Also, the authors conclude on the subject. Analyze forensic investigative practices on this topic.Key words: medical staff, the subject of crime, official, subjective side.